UNICORN Babies: Understanding Circulating and Cerebral Creatine Levels of the Preterm Infant. An Observational Study Protocol - Berry, Mary J.; Schlegel, Melissa; Kowalski, Greg M.; Bruce, Clinton R.; Callahan, Damien L.; Davies-Tuck, Miranda L.; Dickinson, Hayley; Goodson, Angus; Slocombe, Angie; Snow, Rod J.; Walker, David W.; Ellery, Stacey J. (Frontiers in Physiology, 2019)
Creatine is an essential metabolite for brain function, with a fundamental role in cellular (ATP) energy homeostasis. It is hypothesized that preterm infants will become creatine deplete in the early postnatal period, due to premature delivery from a maternal source of creatine and a limited supply of creatine in newborn nutrition. This potential alteration to brain metabolism may contribute to, or compound, poor neurological outcomes in this high-risk population. Understanding Creatine for Neurological Health in Babies (UNICORN) is an observational study of circulating and cerebral creatine levels in preterm infants. We will recruit preterm infants at gestational ages 23+0-26+6, 27+0-29+6, 30+0-32+6, 33+0-36+6, and a term reference group at 39+0-40+6 weeks gestation, with 20 infants in each gestational age group. At birth, a maternal capillary blood sample as well as a venous cord blood sample will be collected. For preterm infants, serial infant plasma (heel prick), urine, and nutrition samples (total parenteral nutrition [TPN], breastmilk or formula) will be collected between birth and term ‘due date’. Key feto-maternal information including demographics, smoking status and maternal diet will also be collected. At term corrected postnatal age (CPA), each infant will undergo an MRI/ 1H-MRS scan to evaluate brain structure and measure cerebral creatine content. A general movement assessment (GMA) will also be conducted. At 3 months CPA, infants will undergo a second GMA as well as further neurodevelopmental evaluation using the Developmental Assessment of Young Children – Second Edition (DAYC-2) assessment tool. The primary outcome measures for this study are cerebral creatine content at CPA, and plasma and urine creatine and guanidinoacetate (creatine precursor) concentrations in the early postnatal period. We will also determine associations between [1] creatine levels at term CPA and neurodevelopmental outcomes (MRI, GMA and DAY-C); [2] dietary creatine intake, circulating and cerebral creatine content; and [3] creatine levels and maternal characteristics (age, diet, smoking). Novel approaches are needed to try and improve preterm-associated brain injury. Inclusion of creatine in preterm nutrition may better support ex utero brain development through improved cerebral cellular energy availability during a period of significant brain growth and development.